Yachting tourist expenditure and its effect on the local economy: The case of Lefkada - Diakomichalis, Nikolaos-Marios; Kalantonis, Petros; Diakomihalis, Mihail (International Conference on Business and Economics - Hellenic Open University, 2025)
The present research examines the economic effects of marine tourism in Lefkada, an island which in recent years has seen great tourism development, especially in marine tourism. The research focused on sailing boats and motorboatsmainly, that is, those that make up the Yachting activity. For our research, it was considered appropriate to create a questionnaire, which covered all the possible expenses of the passenger-tourists of a yacht during their trip. The tourism expenditure made by those on board the tourist boats is converted into income that flows into the businesses of the local and wider economy, as well as into public revenue through the payment of taxes and fees. The benefits from the yachting activity as well as from the operation of the marinas work multiplicatively in the economy both at the local and at the national level. JEL Classifications: H710, L830, P440, R290 Keywords: Yachting, tourist expenditure, local economy, Lefkada, Greece